A Study Pattern of Poisoning among the Autopsies Conducted at Adichunchanagiri Institute of Medical Sciences (Medico Legal Update, 2019)
A Prospective analysis of poisoning deaths was conducted at Department of forensic medicine and Toxicology, Adichunchanagiri Institute of medical sciences and research Centre, B.G Nagar over a period of eighteen months(June 2012 to December 2013).Out of the total 160 autopsies conducted in the mentioned period, deaths due to poisoning comprised 35 cases( 21.8%) cases. The data was analyzed with respect to age, sex, marital status, motive and type of poisoning. It was observed that the incidence of poisoning was highest in the age group of 31-40years (33.7%) followed by 21-30years (22.6%). Male (61.8%) preponderance was more over female (38.2%) and married (60.8%) outnumbered the unmarried (39.2%) in both sexes. The most common type of poisons consumed were organ phosphorus (65.71%). The common reasons of consuming poison were financial constraints (24.28%) followed by marital conflicts (17.28%). This study aims at highlighting the general pattern and factors associated with poisoning deaths. This epidemic of poisoning should be addressed on priority basis and information regarding the adverse effects of poisoning should be disseminated at all levels.